(untitled) (Research, Society and Development, 2020)
The article aim approximations of pillars and features of Trandisciplinarity – third included, complexity, levels of reality, rigor, opening and tolerance – with Martin Heidegger´s phenomenologic notions – care, anguish, existence, opening and closing of sense – like possibilities of contributions for Daseinsanalitic Psychotherapic Clinical or Daseinsanalyse. In this clinical practice, there is no reduction of person in body, mind or diagnostic; the illness has a correlation with patient’s being in the world. Through a bibliographical research metodology, "Walking" broach the possibility of a transdisciplinar consider whole Daseinsanalyse, broadening the psychotherapeutic practice comprehension while privileged mode of care with human existence.